Rebound effect in subglottic hemangioma treated with propranol. Usefulness of the association propranolol-corticosteroids. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 3-month-old little girl was admitted for severe inspiratory dyspnea arising during an inflammatory episode of the upper respiratory tract. An otolaryngology examination, magnetic angioresonance (Fig. 1) and laryngoscopy led to the diagnosis of subglottic hemangioma. She started therapy with propranolol at a dose of 2 mg/kg per day that induced a rapid improvement of inspiratory dyspnea; the latter regressed completely after 3 weeks of therapy. This was continued until one year of life and then withdrawn gradually. 20 days after the suspension inspiratory dyspnea recurred. She then resumed therapy with propranolol 2mg/kg per day associated with deflazacort 1 mg/kg per day. Dyspnea regressed promptly, deflazacort was continued for 3 months at doses progressively tapered and propranolol was withdrawn 5 months after the start of the second cycle. 6 months after the suspension there was no recurrence of dyspnea.